Flax Growing in Tyumen Region: History of Formation and Development in XX Century - V. V. Aksarin; K. P. Korolev (Научный диалог)
The aspects of the origin, formation and development of the flax-growing industry in the Tyumen region in the ХХ century are considered. Based on the available historiographic material (articles, reports, essays, descriptions, statistical information), the authors identified the features of the formation of the industry. It is noted that the historical conditions in which the Tobolsk (Tyumen) province was located, later the region, throughout the XX century, were full of contradictions and difficulties. It is argued that, having good potential, having received an impetus for development in the middle of the last century, at present, flax growing has not become one of the most important sectors of the economy. It is shown that the publications of the Tobolsk Provincial Statistical Committee: “Reviews of the Tobolsk Governorate”, “Reviews of the Tobolsk Governorate in the Agricultural Relationship”, the works of N. L. Skalozubova — reveal the state of agricultural life of the population of the province, the research potential of the Tyumen experimental station, the advanced experience of agricultural enterprises, allow to identify the main problems and prospects for growing flax in the region. The productivity of flax in various agro-ecological zones of the region, varietal potential and the degree of its realization, taking into account climatic features over a long period, the economic feasibility of growing both fiber and oil-bearing forms are analyzed. The main stages of development of flax growing and limiting factors for the production of high-quality flax products are identified.